From Logic to Art. Themes from Nelson Goodman - Ernst, Gerhard (Philosophische Forschung / Philosophical Research, 2009)
Nelson Goodman (1906-1998) was one of the outstanding thinkers of the 20th century. In a memorial note, Hilary Putnam considers him to be "one of the two or three greatest analytic philosophers of the post-World War II period". Goodman has left his mark in many fields of philosophical investigation: Epistemology, Philosophy of Science, Logic, Metaphysics, the General Theory of Symbols, Philosophy of Languageand Philosophy of Art, all have been challenged and enriched by the problems he has shown up, the projects he developed from them and the solutions he has suggested. In August 2006 a couple of Goodman aficionados met in Munich to celebrate the Centennial. The proceedings of the ensuing international conference are documented in this volume. The contributions attest the fact that Goodman's thinking still holds many treasures.